General form of a quadratic equation is
![ax^2+bx+c=0](https://img.qammunity.org/2023/formulas/mathematics/high-school/mvkhuzwnjhb4epaf7jjcoq2vi4zdi4350m.png)
another form is
![(x+h)(x+k_{})=0](https://img.qammunity.org/2023/formulas/mathematics/college/4epv36dbubqyn5k65uqk4o33nkpxhpdf11.png)
where h and k are the number opposite by the sign of the solutions, then on this case the values of h and k are 2 and -6
![(x+2)(x-6)=0](https://img.qammunity.org/2023/formulas/mathematics/college/g49r8ci0o39yf318flhgr0gf58z99menhs.png)
Our equatio is a parabola then if we find the vertex we are finding the axis of simmetry
to find the vertex we trasnforme ou equation to the general form of a quadratic equation multipliying parenthesis
![\begin{gathered} (x* x)+(x*-6)+(2* x)+(2*-6)=0 \\ x^2-6x+2x-12=0 \\ x^2-4x-12=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/19ivmhb1ip2wmqqnby13zzpiac3mac9gje.png)
now take the equation and derivate
![\begin{gathered} 2x-4-0=0 \\ 2x-4=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/o7gjqqvue9cu84xpi05yufdmyaixtrnvm4.png)
if we solve x we find the coordinate x of the vertex and the axis of simmetry
then
![\begin{gathered} 2x-4=0 \\ 2x=4 \\ x=(4)/(2) \\ \\ x=2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/p9g6lxq6bvny2nxnthnlzrbn6l74sfyeyv.png)
axis of Symmetry is x=2